The Beginning of the End: Initial Steps in the Degradation of Plasma Membrane Proteins - Schwihla, Maximilian; Korbei, Barbara (Frontiers in Plant Science, 2020)
The plasma membrane (PM), as border between the inside and the outside of a cell, is densely packed with proteins involved in the sensing and transmission of internal and external stimuli, as well as transport processes and is therefore vital for plant development as well as quick and accurate responses to the environment. It is consequently not surprising that several regulatory pathways participate in the tight regulation of the spatiotemporal control of PM proteins. Ubiquitination of PM proteins plays a key role in directing their entry into the endo-lysosomal system, serving as a signal for triggering endocytosis and further sorting for degradation. Nevertheless, a uniting picture of the different roles of the respective types of ubiquitination in the consecutive steps of down-regulation of membrane proteins is still missing. The trans-Golgi network (TGN), which acts as an early endosome (EE) in plants receives the endocytosed cargo, and here the decision is made to either recycled back to the PM or further delivered to the vacuole for degradation. A multi-complex machinery, the Endosomal Sorting Complex Required for Transport (ESCRT), concentrates ubiquitinated proteins and ushers them into the intraluminal vesicles (ILVs) of multi-vesicular bodies (MVBs). Several ESCRTs have ubiquitin binding subunits, which anchor and guide the cargos through the endocytic degradation route. Basic enzymes and the mode of action in the early degradation steps of PM proteins are conserved in eukaryotes, yet many plant unique components exist, which are often essential in this pathway. Thus, deciphering the initial steps in the degradation of ubiquitinated PM proteins, which is the major focus of this review, will greatly contribute to the larger question of how plants mange to fine-tune their responses to their environment.